The saccus vasculosus of fish is a sensor of seasonal changes in day length - Nakane, Yusuke; Ikegami, Keisuke; Iigo, Masayuki; Ono, Hiroko; Takeda, Korenori; Takahashi, Daisuke; Uesaka, Maiko; Kimijima, Meita; Hashimoto, Ramu; Arai, Natsumi; Suga, Takuya; Kosuge, Katsuya; et al. (Nature communications, 2013)
The pars tuberalis of the pituitary gland is the regulatory hub for seasonal reproduction in birds and mammals. Although fish also exhibit robust seasonal responses, they do not possess an anatomically distinct pars tuberalis. Here we report that the saccus vasculosus of fish is a seasonal sensor. We observe expression of key genes regulating seasonal reproduction and rhodopsin family genes in the saccus vasculosus of masu salmon. Immunohistochemical studies demonstrate that all of these genes are expressed in the coronet cells of the saccus vasculosus, suggesting the existence of a photoperiodic signalling pathway from light input to neuroendocrine output. In addition, isolated saccus vasculosus has the capacity to respond to photoperiodic signals, and its removal abolishes photoperiodic response of the gonad. Although the physiological role of the saccus vasculosus has been a mystery for several centuries, our findings indicate that the saccus vasculosus acts as a sensor of seasonal changes in day length in fish. The saccus vasculosus is a circumventricular organ of the hypothalamus of many jawed fish whose function has remained a mystery for more than 300 years. Here the authors provide evidence that the saccus vasculosus functions as a sensor of seasonal changes in day length.